2019
DOI: 10.3390/atmos10060302
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Risk Assessment of Particulate Matter and Volatile Organic Compounds in Metro Carriage in Shanghai, China

Abstract: Air quality in transportation microenvironment has received widespread attention. In this study, the exposure levels of volatile organic compounds (VOCs) and particulate matter that have a diameter of less than 2.5 micrometers (PM2.5) in Shanghai metro system were measured simultaneously, and their risks to human health under different driving conditions were then assessed. The results showed that VOCs, PM2.5 concentrations and life cancer risk (LCR) of four VOCs (benzene, formaldehyde, ethylbenzene, and aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 42 publications
(70 reference statements)
2
25
0
Order By: Relevance
“…The mean level in Nanjing, also located in Yangtze River Delta, was 54 μg/m 3 ( Shen and Gao, 2019 ). Several studies conducted in Shanghai before the pandemic (in 2013, 2015, 2016 and 2017) reported the average levels from 24 to 84 μg/m 3 ( Gong et al, 2019 ; Peng et al, 2021 ; Wang et al, 2016b ; Xu et al, 2016 ). In the present study, the mean PM 2.5 concentration on subway was 17 μg/m 3 , ranging from 7 to 35 μg/m 3 , lower than the observations in the pre-pandemic period.…”
Section: Resultsmentioning
confidence: 99%
“…The mean level in Nanjing, also located in Yangtze River Delta, was 54 μg/m 3 ( Shen and Gao, 2019 ). Several studies conducted in Shanghai before the pandemic (in 2013, 2015, 2016 and 2017) reported the average levels from 24 to 84 μg/m 3 ( Gong et al, 2019 ; Peng et al, 2021 ; Wang et al, 2016b ; Xu et al, 2016 ). In the present study, the mean PM 2.5 concentration on subway was 17 μg/m 3 , ranging from 7 to 35 μg/m 3 , lower than the observations in the pre-pandemic period.…”
Section: Resultsmentioning
confidence: 99%
“…Third, the PM-VOC data gap, associated with site-outgassed VOCs, should be remedied because VOC-risk-data studies are feasible. For years, scientists have quantitatively assessed the increased human-health and smog risks associated with PM-and-adhering-VOCs [148][149][150][151][152][153][154].…”
Section: Airborne-exposure Data Gaps Especially For Particulate-metamentioning
confidence: 99%
“…The instrument was either placed at the passenger's breathing level or carried in a backpack by the researcher. 8,9,24,[27][28][29][30][31][32][33][34][35]39,[41][42][43]47,57,58,65,67,69,70,76,78,79,81,82,[85][86][87]90 The real-time mass concentration of PMs was determined by DustTrak using light scattering technology and can detect PM 2.5 and PM 10 mass concentrations. On the other hand, the Dustmate fume and dust detector was another standard instrument observed in the selected articles for this review.…”
Section: Methods Of Data Collection/ Instrumentationmentioning
confidence: 99%
“…From the eligible articles measuring the in-train concentration of PMs, 52% of the studies were performed in Asia, with China having a more significant fraction of 29 publications, as shown in Figure 3. From the publications in China, Shanghai has a total of six publications, [26][27][28][29][30][31] followed by Hong Kong with five publications, [32][33][34][35][36] Beijing with four publications, 23,[37][38][39] Taiwan with three publications, [40][41][42] Nanjing and Xi'an have two publications each, [43][44][45][46] and Guangzhou, 47 Foshan, 48 Suzhou, 49 Tianjin, 9 Yangtze 50 and Zhengzhou, 51 have one publication each. A publication was also found for the northern part of China.…”
Section: Study Locationmentioning
confidence: 99%